Design, synthesis and cytotoxic evaluation of o-carboxamido stilbene analogues - Azmi, Mohamad Nurul; Md Din, Mohd Fadzli; Kee, Chin Hui; Suhaimi, Munirah; Ang, Kheng Ping; Ahmad, Kartini; Nafiah, Mohd Azlan; Thomas, Noel Francis; Leong, Kok Hoong; Awang, Khalijah (MDPI, 2013)
Resveratrol, a natural stilbene found in grapes and wines exhibits a wide range of pharmacological properties. Resveratrol is also known as a good chemopreventive agent for inhibiting carcinogenesis processes that target kinases, cyclooxygenases, ribonucleotide reductase and DNA polymerases. A total of 19 analogues with an amide moiety were synthesized and the cytotoxic effects of the analogues on a series of human cancer cell lines are reported. Three compounds 6d, 6i and 6n showed potent cytotoxicity against prostate cancer DU-145 (IC50 = 16.68 µM), colon cancer HT-29 (IC50 = 7.51 µM) and breast cancer MCF-7 (IC50 = 21.24 µM), respectively, which are comparable with vinblastine. The resveratrol analogues were synthesized using the Heck method.